2016
DOI: 10.1073/pnas.1609222113
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Star Carr on the vulnerability of organic archaeological remains to environmental change

Abstract: Examples of wetland deposits can be found across the globe and are known for preserving organic archaeological and environmental remains that are vitally important to our understanding of past human-environment interactions. The Mesolithic site of Star Carr (Yorkshire, United Kingdom) represents one of the most influential archives of human response to the changing climate at the end of the last glacial in Northern Europe. A hallmark of the site since its discovery in 1948 has been the exceptional preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…These agents preferentially attack polysaccharides via enzymatic degradation, with hemi-celluloses being particularly vulnerable [15,20]. Some studies demonstrate that chemical deterioration of cellulose also occurs in waterlogged environments, particularly under extreme conditions such as low pH [6,10]. Lignin is generally considered to be much more resistant to biological decay, largely due to its highly stable structure: a large 3 dimensional network of cross-linked polyphenol sub units ( Fig.…”
Section: The Structure and Decay Of Waterlogged Archaeological Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents preferentially attack polysaccharides via enzymatic degradation, with hemi-celluloses being particularly vulnerable [15,20]. Some studies demonstrate that chemical deterioration of cellulose also occurs in waterlogged environments, particularly under extreme conditions such as low pH [6,10]. Lignin is generally considered to be much more resistant to biological decay, largely due to its highly stable structure: a large 3 dimensional network of cross-linked polyphenol sub units ( Fig.…”
Section: The Structure and Decay Of Waterlogged Archaeological Woodmentioning
confidence: 99%
“…Assessing the current state of preservation of waterlogged archaeological wood provides vital information on decay trajectories, archaeological significance (the state of preservation is likely to influence the level of detail that can be retrieved from an object), and the potential consequences of changing conditions [1,2]. Appropriate analysis establishes a robust baseline against which any further deterioration can be tracked, for example: when a site is being monitored [3,4], when comparing material from different sites or phases of investigation [5,6], or when gathering experimental data on decay mechanisms [7][8][9]. Analysis is also important post-excavation; detecting decay over periods of storage or display can help identify when conditions are not conducive to the continued survival of an object [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…By investigating the soil chemical properties and by relating them to bone histological analyses, collagen preservation and the palaeobotany at the site, questions of how organic preservation has changed during the last seven decades and what might have caused the changes are answered and discussed. The present study shall be viewed as a part of investigating the prerequisites for the future survival of our long-term archaeo-environmental archive of climatic and environmental changes and/or its relation to past human cultural interaction [2][3][4][5][6][7][8][9], in a time when reports of ongoing and accelerated destruction of this valuable record emerge from all over the world [1,[10][11][12][13][14][15][16][17][18][19][20][21][22]. settlements where section A, C and HC intersect one settlement and Ageröd I:B and I:D intersects two others [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the past few decades there has been considerable debate over the interpretation of the site (e.g. Andresen et al 1981;Caulfield 1978;Conneller 2000;Jacobi 1978;Legge/Rowley-Conwy 1988;Pitts 1979;Price 1982) as well as concerns over the deteriorating levels of organic preservation (Boreham et al 2011a;b;High et al 2016;Milner 2007;Milner et al 2011a;b). As a result new research has been carried out at Star Carr which has led to a fundamentally new understanding of the site.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this work also showed that the levels of organic preservation were very poor; the few pieces of antler and bone found were severely desiccated and in some cases had turned to jelly. Scientific analysis showed that this had been brought about by a lowering of the water-table caused through drainage, and subsequent changes to the soil chemistry causing a massive increase in acidity (Boreham et al 2011a;b;High et al 2016;Milner 2007;Milner et al 2011a).…”
mentioning
confidence: 99%